A rare case of recurrent urinary tract infection due to Trichosporon species in an immune-competent diabetic female patient - Adhikari, Saroj; Saud, Bhuvan; Paudel, Govinda; Wagle, Sunita (Archives of Case Reports, 2019)
Trichosporonosis is a disease caused by Trichosporon spp. which are ubiquitous anamorphic yeast that commonly inhabit the soil. In human they are found in the skin, gastrointestinal tract and respiratory tract. Globally, Trichosporon spp. infection is rare and remains scantily reported in urinary tract infections and disseminated invasive infection amongst immunocompromised and cancer patients with neutropenia. Trichosporon asahii is the most commonly reported species. Virulence factors like proteinases, lipases, and phospholipases may be responsible for disease manifestation. We report a case of recurrent urinary tract infection due to Trichosporon spp. in a 62-year-old immunocompetent diabetic female which remained misdiagnosed for a long period of time. The patient was subsequently treated successfully by oral fluconazole drug.